Sharia Accounting Perspective on Data Collection for Creative Industry Micro, Small and Medium Enterprises (MSMEs) - Kamilah, Kamilah; Sumartono, Eko; Parwito, Parwito (BIMA Journal (Business, Management, & Accounting Journal), 2024)
Purpose: This research aims to analyze the role of the Department of Industry, Trade, Energy, and Mineral Resources (Disperindag ESDM) of North Sumatra Province in collecting data on creative industries among MSMEs in Medan using a sharia accounting framework. Methodology: The method used is literature research to understand the concepts and principles of sharia accounting, as well as interviews with stakeholders in Medan City to understand the practices applied in developing the MSME creative industry. Results: The study identifies several problems in data collection on Small and Medium Industries (IKM) by the ESDM Industry and Trade Service of North Sumatra Province. Findings: Challenges include difficulty in timely and accurate data collection, especially in remote areas, which affects the quality of the information obtained. Additionally, limited human resources hinder the effectiveness and efficiency of data collection and analysis. Novelty: This research provides insights into the application of sharia accounting principles in the data collection process for MSMEs. Originality: The study offers a detailed analysis of the role of a provincial department in the context of sharia accounting for MSMEs. Conclusions: Addressing the challenges in data collection can improve the quality of information and support the development of the creative industry among MSMEs in Medan. Type of Paper: Empirical Research Article.